Trust and Trustworthy Computing 5th International Conference, TRUST 2012, Vienna, Austria, June 13-15, 2012. Proceedings - Katzenbeisser, Stefan; Weippl, Edgar; Camp, L. Jean.; Volkamer, Melanie; Reiter, Mike.; Zhang, Xinwen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 5th International Conference on Trust and Trustworthy Computing, TRUST 2012, held in Vienna, Austria, in June 2012. The 19 revised full papers presented were carefully reviewed and selected from 48 submissions. The papers are organized in two tracks: a technical track with topics ranging from trusted computing and mobile devices to applied cryptography and physically unclonable functions, and a socio-economic track focusing on the emerging field of usable security.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Data Encryption; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Computers and Society; Information Systems Applications (incl. Internet).